REM Sleep Behaviour Disorder in Multiple System Atrophy: From Prodromal to Progression of Disease - Giannini, Giulia; Provini, Federica; Cortelli, Pietro; Calandra-Buonaura, Giovanna (Frontiers in Neurology, 2021)
A higher frequency of motor and breathing sleep-related disorders in Multiple System Atrophy (MSA) populations is reported. REM sleep behaviour disorder (RBD) is one of the most robust markers of an underlying alpha-synucleinopathy. Although a large corpus of literature documented the higher prevalence of RBD in MSA, few studies have systematically investigated the prevalence of RBD as mode of disease onset and its role in disease progression. Moreover, there has been increasing interest in phenoconversion into synucleinopathies of cohorts of patients with isolated RBD (iRBD). Finally, some studies investigated RBD as predictive factor of conversion in Isolated Autonomic Failure, a synucleinopathy presenting with autonomic failure as the sole clinical manifestation that could convert to a manifest central nervous system synucleinopathy. As the field of neurodegenerative disorders moves increasingly toward developing disease-modifying therapies, detecting individuals in the prodromal stage of these synucleinopathies becomes crucial. The aims of this review are to summarize: 1) the prevalence of RBD during the course of MSA and as presenting feature of MSA (iRBD); 2) the RBD features in MSA; 3) MSA progression and prognosis in the subgroup of patients with RBD predating disease onset; 4) the prevalence of MSA conversion in iRBD cohorts. Moreover, we summarize previous results on the role of RBD in the context of Isolated Autonomic Failure as marker of phenoconversion to other synucleinopathies and, in particular, to MSA.